1987
DOI: 10.1002/srin.198700857
|View full text |Cite
|
Sign up to set email alerts
|

Development of thermo-mechanical treatments of a maraging steel for yield strengths above 3 GPa

Abstract: Hot‐rolling of austenite and cold‐rolling of martensite were combined with aging treatments to obtain new microstructures in a maraging steel with a high Mo‐content. Purpose of the investigation is to acquire an optimum combination of ultra high yield stress (σr>3000 MPa) and ductility (or toughness). The best results were obtained by treatments consisting of high amounts of plastic deformation between 1000°C and 600°C (ausforming) and aging of the martensite which had formed from the deformed austenite. Ausag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…This thermal stability is of the carbon free lath martensite microstructure/has been used to achieve a further increase of strength by the precipitation of intermetallic phases [5]. The tensile strength of these alloys, called Maraging Steels, reached up to 3000 MPa at a total elongation'of 2,5 % [6].…”
Section: Introductionmentioning
confidence: 99%
“…This thermal stability is of the carbon free lath martensite microstructure/has been used to achieve a further increase of strength by the precipitation of intermetallic phases [5]. The tensile strength of these alloys, called Maraging Steels, reached up to 3000 MPa at a total elongation'of 2,5 % [6].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that the YS of 400 ksi (2760 MPa) seems to represent an upper boundary for the maraging steels with 18%Ni 23 and that the lower limit for the 13%Ni-15%Co-Mo-Ti 12,13,24 maraging steels. The characteristics and particularities of the precipitation hardening of these new ultra-high-strength maraging steels have been studied with the help of transmission electron microscopy 12,24,26,27 and have shown that after aging the reiterated presence of three types of nanometric sized precipitates: (Ni,Fe) 3 (Mo,Ti); μ-(Fe,Co) 7 Mo 6 and the Laves phase (Fe,Co) 2 (Mo,Ti). On the other hand, several characteristics of the phase transformations and the hardening mechanisms acting in this new class of maraging steels require complementary and more detailed studies.…”
Section: Introductionmentioning
confidence: 95%
“…Among the ultra-high-strength materials, available in the market in the various geometries and produced by wellknown processes, maraging steels must be pointed out, that can present a YS over 3 GPa 12 . In the Fe-Ni system, the base for the maraging steels, man has been using them before the discovery of the chemical element Ni (in 1751), and before the birth of the commercial Ni-alloyed steels, around 1888/1889 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deve-se mencionar que as corridas pesquisadas no presente trabalho são baseadas em trabalho anterior, no qual foram obtidos, após tratamentos termomecânicos adequados, limites de escoamento acima de 3 GPa [11].…”
Section: Objetivos Do Trabalhounclassified